Studi Diagnostik Pengembangan Usahatani Kedelai di Desa Karyamukti, Kabupaten Karawang - Maesti Mardiharini; nFN Muchlas; M. Taufik; Tahlim Sudaryanto (Jurnal Agro Ekonomi, 1990)
EnglishAn identification of a prospect and constraints of soybean production is needed to establish whether a certain region is suitable or not for such a crop. By means of collecting indepth information from soybean and non-soybean farmers, coupled with group interviews and information from the key informan, the following results are reported. Soybean farming is mostly undertaken by small farmer and landless laborer in the second dry season. Major factors motivating farmers to grow soybean is due to the availability of land, free of charge. Farmer's practices on soybean farming is still traditional and is far from those recommended. Taking into consideration the available resources, it is concluded that soybean farming can be expanded in the study site, if the major constraints are alleviated. The lack of high quality seed, low plant density, inappropriate fertilizer and insecticides application are among technical constraints which might be solved by more intensive extension program involving farmer groups. Family and hired labor competition need attention by applying labor saving technology. Relatively low degree of group activities and the existence of mutual relationship between land owner and laborer are social constraints observed in the area. These constraints require proper action considering both the objective of increasing soybean production and employment/income generation for the laborer.IndonesianIdentifikasi potensi dan kendala dalam usahatani diperlukan untuk mengetahui apakah suatu wilayah mampu dijadikan sasaran program pengembangan usahatani kedelai. Dengan menggali informasi mendalam terhadap petani kedelai dan non kedelai, diperkuat dengan wawancara kelompok dan informan kunci, diperoleh hasil sebagai berikut. Usahatani kedelai umumnya dilakukan oleh buruhtani dan petani berlahan sempit pada musim kemarau (MK) II. Motivasi mereka menanam kedelai terutama atas pertimbangan penggunaan lahan yang tanpa membayar sewa. Cara bercocok tanam pola petani cenderung masih tradisional dan belum sesuai dengan paket anjuran. Berdasarkan potensi yang ada, dapat disimpulkan bahwa usahatani kedelai dapat dikembangkan di daerah penelitian, dengan mempertimbangkan beberapa faktor yang menjadi kendala. Kurangnya pengadaan benih, populasi tanaman yang belum optimum, pemupukan dan pengendalian hama yang belum intensif, semuanya adalah kendala fisik/teknis yang dapat diatasi dengan memberikan informasi/bimbingan melalui PPL ke kelompok tani. Adanya kompetisi tenaga kerja di dalam dan luar keluarga perlu pemecahan masalah dengan pemakaian teknologi yang hemat tenaga kerja. Aktivitas kelompok yang masih rendah dan adanya hubungan "pemilik lahan- buruhtani", merupakan kendala sosial yang perlu dicari jalan tengah antara kepentingan pemerataan kesempatan kerja/pendapatan dengan peningkatan produksi kedelai.